Detection of Bacillus anthracis Spores Using Peptide Functionalized SERS-Active Substrates. (2nd October 2012) - Sengupta, Atanu; Shende, Chetan; Farquharson, Stuart; Inscore, Frank
Abstract : The need for portable technologies that can rapidly identify biological warfare agents (BWAs) in the field remains an international priority as expressed at the 2011 Biological Weapons Convention. In recent years, the ability of surface-enhanced Raman spectroscopy (SERS) to rapidly detect various BWAs at very low concentrations has been demonstrated. However, in the specific case of Bacillus anthracis, differentiation at the species level is required since other bacilli are common in the environment, representing potential false-positive responses. To overcome this limitation, we describe the use of a peptide attached to the SERS-active metal that selectively binds Bacillus anthracis -Sterne as the target analyte. Using this approach, 10 9    B. anthracis -Sterne spores/mL produced an intense dipicolinic acid spectrum upon the addition of acetic acid, while the same concentration and treatment of B. cereus and B. subtilis did not.